The interaction of D mesons and nucleons at finite density - Antunes, S. M. [UNESP]; Krein, G. [UNESP] (My University, 2008)
We present results on the the influence of changes in the masses and sizes of D mesons and nucleons on elastic DN scattering cross sections and phase shifts in a hadronic medium composed of confined quarks in nucleons. We evaluate the changes of the hadronic masses due to changes of the light constituent quarks at finite baryon density using a chiral quark model based on Coulomb gauge QCD. The model contains a confining Coulomb potential and a transverse hyperfine interaction consistent with a finite gluon propagator in the infrared. We present results for the total cross section and the s-wave phase shift at low energies for isospin I=1-for I=0 and other partial waves the results are similar.
Keywords: Baryon density; Chiral quark models; Coulomb gauge; Coulomb potential; D-mesons; Finite density; Hyperfine interactions; Isospin; Partial waves; Scattering cross section; Total cross section; Bosons; Electric fields; High energy physics; Phase shift; Hadrons